2013
DOI: 10.1155/2013/348248
|View full text |Cite
|
Sign up to set email alerts
|

What Works and What Does Not: A Discussion of Popular Approaches for the Abandonment of Female Genital Mutilation

Abstract: The prevalence of Female Genital Mutilation (FGM) is reducing in almost all countries in which it is a traditional practice. There are huge variations between countries and communities though, ranging from no change at all to countries and communities where the practice has been more than halved from one generation to the next. Various interventions implemented over the last 30–40 years are believed to have been instrumental in stimulating this reduction, even though in most cases the decrease in prevalence ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 19 publications
5
108
2
1
Order By: Relevance
“…Moreover there is no synthesis of current research to inform the design of midwifery education programs or supportive workplace practice in both LMIC and HIC settings. Reviews to date have focused on nursing care (Terry & Harris, 2013), health professional training in Africa (Berg & Denison, 2012;Berg & Denison, 2013), or have provided a broad discussion of peer reviewed and grey literature on health professional training (Johansen et al, 2013). To address the gap in the literature, we undertook a review of the peer reviewed literature to examine the experiences and needs of midwives in LMIC and HIC to endeavour to provide more insight for educators and policy makers.…”
Section: Need For a Narrative Synthesismentioning
confidence: 99%
“…Moreover there is no synthesis of current research to inform the design of midwifery education programs or supportive workplace practice in both LMIC and HIC settings. Reviews to date have focused on nursing care (Terry & Harris, 2013), health professional training in Africa (Berg & Denison, 2012;Berg & Denison, 2013), or have provided a broad discussion of peer reviewed and grey literature on health professional training (Johansen et al, 2013). To address the gap in the literature, we undertook a review of the peer reviewed literature to examine the experiences and needs of midwives in LMIC and HIC to endeavour to provide more insight for educators and policy makers.…”
Section: Need For a Narrative Synthesismentioning
confidence: 99%
“…In 37 the fifteen years that followed, programmes aimed at reducing FGM emphasised the health risks of the practice, as this was felt to be the most acceptable and sensitive way to challenge the problem. Whilst a human rights approach has now been introduced to tackle FGM (see Section 1.6) raising awareness of the health impacts of FGM amongst practicing communities continues to be the preferred tool used to end FGM (Johansen et al, 2013).…”
Section: Figure 12 the Possible Health Impacts Of Fgmmentioning
confidence: 99%
“…In 37 the fifteen years that followed, programmes aimed at reducing FGM emphasised the health risks of the practice, as this was felt to be the most acceptable and sensitive way to challenge the problem. Whilst a human rights approach has now been introduced to tackle FGM (see Section 1.6) raising awareness of the health impacts of FGM amongst practicing communities continues to be the preferred tool used to end FGM (Johansen et al, 2013).The effectiveness of stressing the health impacts of FGM in order to end the practice in the EU is being questioned by many researchers and interventionists (Johansen et al, 2013).REPLACE suggests that the reason that this 'health approach' has had limited success in ending FGM is because it does not treat FGM as a social norm, with different communities having different belief systems and being at different stages of readiness to end the practice.Whilst raising awareness of the health impacts of FGM, the approach does not provide communities and individuals with the necessary tools to challenge the social norm which supports FGM enabling behavioural change to occur. …”
mentioning
confidence: 99%
“…Lessons from other countries have shown that successful programs against female genital mutilation require long-term commitment to induce/support behaviour change at community level and capacitate enforcement mechanisms through communities of practice across health, education and law enforcement sectors [16][17][18][19][20]. The close tethering of the practice to ethnic and religious communities in Sri Lanka warrants a careful calibration of actors, where evidence-based and community participatory approach is needed.…”
Section: Stakeholdersmentioning
confidence: 99%
“…Evidence from other countries have shown that efforts to curb female genital mutilation relies on the strength of community advocates, legal experts, researchers, clinicians and administrators working at local, regional and national levels [16][17][18]. First and foremost, this requires courage on the part of us, the medical professionals.…”
Section: Point Of Viewmentioning
confidence: 99%